Refining the Displacement of Culture and the Use of Scenes and Themes in Organizational Studies - Morey, Nancy C.; Luthans, Fred (Academy of Management Review, 1985)
Nancy C. Morey, Fred Luthans, Refining the Displacement of Culture and the Use of Scenes and Themes in Organizational Studies, The Academy of Management Review, Vol. 10, No. 2 (Apr., 1985), pp. 219-229